Histology of the endothermic opah (Lampris sp.) suggests a new structure–function relationship in teleost fish bone. (30th June 2018) - Davesne, Donald; Meunier, François J.; Friedman, Matt; Benson, Roger B. J.; Otero, Olga
Abstract : Endothermy, production and retention of heat by the body, appeared convergently in mammals, birds and four spiny-rayed teleost fish lineages. Of these, red-muscle endothermy over most or all of the body has only appeared in two groups: tunas and the opah ( Lampris ). Hitherto, tunas have been the only spiny-rayed fishes known to have bones containing embedded osteocyte cells; others have acellular bone. We examined bone histology in Lampris for the first time, demonstrating the presence of cellular bone very similar to that of tunas. This contrasts with the acellular condition of its ectothermic close relatives. The distribution of this character suggests that it co-evolved with red-muscle endothermy, hinting at a common physiological mechanism that would link bone histology to endothermy in these distantly related teleost lineages.